(untitled) (Research, Society and Development, 2022)
Objective: To compare the shaping of canals simulated by two rotary instruments: ProTaper Next (Dentsply Maillefer, Ballaigues, Switzerland) and X-Gray after second use. Materials and methods: Sixteen blocks of simulated channels were divided into two groups: PTN (ProTaper Next) and XG (X-Gray). Indian ink was injected into the simulated channels. These were covered with laminated paper so that there is no influence on the instrumentation. Prior to instrumentation of the root canals, patency was performed with a #10 K-file. The shaping of the canals was performed with an endodontic motor (Endopen-Schuster). Pre- and postoperatively, photographic images were analyzed for later superimposition and analysis in image software in Adobe Photoshop CS5.1 (Adobe Systema, San José, USA). Results: The Shapiro-Wilk tests were performed, whose purpose is to verify whether the data present a distribution similar to normal (p > 0.05) or not (p < 0.05). In this case, it is verified whether these variables are normally distributed. Conclusion: It was concluded that both rotary systems proved to be efficient in the modeling of the canals, being able to be used in curved canals.